Evaluating attitude towards communication training in medical graduates and postgraduates: a cross-sectional study in a central institute of North India - Ali J. Abedi; Jhilmil Agrawal; Saira Mehnaz; Mohammad Y. Zubair; Shubham Upadhyay (International Journal Of Community Medicine And Public Health, 2026)
Background: Communication skills play key role in patient satisfaction, fosters trust and empathy. In recognition of this, the attitude, ethics, and communication (AETCOM) module was incorporated into the MBBS curriculum in 2019. The objective of the study is to assess the attitude of medical graduates and postgraduates (PGs) towards communication skill learning programme (CSLP). Methods: This cross-sectional study was conducted in the department of community medicine at Jawaharlal Nehru Medical College, Aligarh Muslim University. A total of 478 were enrolled and categorized into four groups. Participants completed the communication skills attitude scale (CSAS) questionnaire through an online platform. The questionnaire comprised 26 items with positive and negative statements, and three domains of attitude using a five-point likert scale. Differences between groups were analysed using t-test and ANOVA, and data analysis was performed using statistical package for the social sciences (SPSS) version 20.0. Results: The mean scores for positive attitude, negative attitude, affective, cognitive, and respect domains were 36.6±7.0, 54.3±6.2, 43.5±4.6, 17.4±2.1, and 17.0±2.3, respectively. Negative attitude scores differed significantly between newly admitted students and the second (34.4 versus 37.5, p=0.003) and third groups (34.4 versus 37.8, p=0.001), while positive attitudes were similar. Significant differences were also observed in affective (p=0.036) and cognitive (p=0.034) domains between the first and fourth groups, with no significant difference in respect attitudes. Conclusions: Overall positive attitude of students towards communication skills learning. Improved attitudes among interns and PGs may be related to greater clinical exposure, highlighting the importance of integrating communication skills training throughout medical education to enhance quality of care.